ANALISIS POLA KEMITRAAN AGRIBISNIS DI KAMPUNG KUCAI, DUSUN KRANGGAN, KECAMATAN GARUM, KABUPATEN BLITAR - Brillian Pintakami, Lintar; Yan Asdasiwi, Muttia (Viabel : Jurnal Ilmiah Ilmu-Ilmu Pertanian, 2020)
This study aims to provide an overview of the form of agribusiness partnership patterns that take place in Kampung Kucai, as well as analyzing the perceptions of peasant partners in the partnership program. In addition, this study shows whether there are differences in income received by partner farmers and non-partner farmers. The method of determining respondents in this study uses cluster sampling. From the calculation results obtained by the number of samples for Non-Partner farmers as many as 44 farmers. While the sample used for Kucai Mitra farmers was 20 people. In addition there are also 5 key informants Data collection methods carried out in this study there are several kinds of structured interviews, in-depth interviews, participatory observation, and documentation. Data analysis using descriptive analysis, Likert analysis, farming analysis, and statistical analysis of average difference test. The results showed that the type of partnership between the "BRI Bank" Financial Institution and partner chives farmers was classified as a core-plasm partnership pattern. The perception of partner chives farmers to the partnership process with the financial institution "Bank BRI" which has a very good category with a percentage of 80% where the total score is 483. The results of income obtained by partner chives farmers are greater than independent chives farmers, amounting to Rp. 435,075, - / harvest for partner farmers, while independent farmers in the amount of Rp.305,783, - / harvest. The results of the statistical test of the average difference showed that the value of t hit Equal variances not assumed 5.059> 0.05 then HA was accepted and H0 was rejected, so it could be said that there was a significant difference between the income of partners and independent farmers.